(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
A 20 yr old person was sitting on the road in front of a stationary truck and watching the repair of the vehicle by the driver. Suddenly the left front tyre of the truck burst and an ejected tyre piece hit the person on right side chest and lower abdomen. He fell down on the surface due to impact and became unconscious. He was taken to a nearest hospital where pronounced dead. At autopsy, multiple abrasions over the body and fatal liver injury were found. In forensic literature few articles regarding fatal injury due to tyre burst are found, however fatal liver injury due to it is not reported.